Konsep Kepemilikan Islam untuk Akuntansi Syariah - Mugiyati Mugiyati (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2007)
The attempt of creating justice, weathness (social dan economy) and protecting to the ownership is the goal of Islamic accounting and economy. Islam teaches us that everything is created by Allah, it can be owned by human collectively. Juridically, individual human right for owning the thing, such as the right for having, enjoying, and replecing the wealthy, is certified and roled by Islam. However, they have moral responsibility to give their wealthy since the other people (social) are also on the right part of such wealthy. In concerning with the matter, Islamic accounting is trying to activate the activa scoring as an important basic to the treasure that the zakah is suppossed to be paid out.